Bloxel - Developing a voxel game engine in Java using OpenGL - Arnebäck, Eric; Bärring, Felix; Hage, Johan; Lundén, Anton; Löfman, Andreas; Ogeryd, Niclas (My University, 2015)
The purpose of this thesis is to explore the process of creating a voxel game engine, in which features such as procedural terrain generation and world interaction are essential, inspired by pioneering games in the genre such as Minecraft. The thesis discusses the development process in regards to graphics, physics, and game logic. The game engine is written in Java using the Lightweight Java Game Library for graphics and audio, and employs the Ashley framework to implement an entity-component design pattern. The project resulted in a simple voxel game, with a procedurally generated environment and basic player-world physics and interaction.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology